Acolhimento em instituições de longa permanência para idosos sob a ótica dos gestores - Mouta, Carolina (2023)
In Brazil, Long-Term Care Facilities (LTCFs) for the elderly stand out in offering long-term care in the institutional comprehensive collective care model. In this context, managers and qualified professionals are expected to understand the typology and services attributed to these spaces. Objective: To analyze the perception of managers of long-term care facilities for the elderly (LTCFs) regarding the reason for searching for vacancies in these spaces. Methodology: Descriptive-exploratory research of a qualitative and quantitative nature carried out in the city of Araraquara, São Paulo state. The study was divided into 2 stages: 1-Bibliographic review; 2- Online interviews with institution managers. The bibliographic review was systematized using the StArt software. Data collection in the second stage took place through a semi-structured questionnaire on the Google forms platform according to the facilities, the manager's profile, and their perspective on the search for vacancies in the ILPI. Data analysis is based on simple and descriptive statistics observing the frequency and average of the data. Content analysis was done through ordering the material, floating readings, and grouping them into categories based on the frequency of the theme transmitted by managers. All ethical principles in research will be applied. Results: 432 articles were identified, 420 of which were excluded for not being part of the subject and 12 articles that related to the research through the central themes. There were 2 articles on the topic of organizational culture, 4 articles on transformational leadership, 4 articles on perceptions about elderly care and 2 articles on institutional improvements. In relation to institutions in the Municipality of Araraquara in São Paulo State, only 8 of the 17 managers filled out the online form. Regarding the institutions, all were non-governmental, with 7 (87.5%) for-profit and 1 (12.5%) non-profit of the philanthropic type. Most managers are female (37.5%), with an average age of 52.25 years and married status. Managers' perceptions about the reasons that lead to the search for vacancies in institutions stood out in the social (11) and health (8) dimensions. In the social dimension, the predominant category was “Fragility of the family caregiver”, with subcategories such as “Fragility in guidance on care”, “Avoiding social exclusion” and “Absence of caregiver”. Conclusion: According to the managers' perception, there are weaknesses in the care process provided by the informal caregiver. Weaknesses are observed in the training of managers and in the systematization of a database on information on elderly people and family members.